Perceived knowledge and use of IOTN-DHC among dental officers in Sabah - Lee, Jin Han (IIUM Journal of Orofacial and Health Sciences, 2026)
This cross-sectional study assessed the knowledge and use of IOTN-DHC among dental officers in Sabah. A self-administered, anonymous, and structured questionnaire in the format of Google form were used. The questionnaire addressed socio-demographic characteristics, knowledge and use on IOTN-DHC. Data were entered into a standardised collection form and were analysed descriptively and inferentially. All respondents knew IOTN (n=224, 100.00%). More than half used both components (n=115, 51.34%). Most had training on IOTN-DHC (n=187, 83.48%). The main sources of training were workshop or course (n=128, 57.14%) and undergraduate training (n=109, 48.66%). More than half felt confident in using IOTN-DHC (n=135, 60.27%). Dental officers graduated from local public universities (n=54, 80.60%), had working experience five years and above (n=66, 72.53%), and had previous training (n=125, 66.84%) were confident. IOTN-DHC was used to assess treatment eligibility (n=220, 98.21%), to grade malocclusion (n=170, 75.89%), to communicate with colleagues (n=149, 66.52%), and to communicate with patients (n=69, 30.80%). Majority needed more training (n=210, 93.75%). Methods beneficial were hands on workshop or course (n=201, 89.73%), poster in surgery room (n=161, 71.88%), webinar (n=131, 58.48%), online educational materials (n=102, 45.54%), and textbooks (n=66, 29.46%). In conclusion, the perceived knowledge and use of IOTN-DHC among dental officers in Sabah were moderate. Graduated from local public universities, had longer working experience, and had previous IOTN-DHC training contributed to better confidence of the dental officers. Yearly training sessions are important to enhance the knowledge, use, and confidence in using IOTN-DHC.